Effect of fluoride coating on degradation behaviour of unidirectional Mg/PLA biodegradable composite for load-bearing bone implant application. (September 2019) - Ali, Wahaaj; Mehboob, Ali; Han, Min-Gu; Chang, Seung-Hwan
Abstract: Biodegradable composites of unidirectionally reinforced 50-Mg/PLA (50% Mg wire by volume) were investigated to replace conventional non-degradable metallic implants for fixing long-bone fractures. This study presents the advantages of fluoride-coated magnesium alloy AZ31 wires in unidirectionally reinforced Mg/PLA biodegradable composites. The samples were also evaluated for degradation over a duration of 56 days by immersion in phosphate buffered saline solution at the human body temperature of 37 °C; variations in wet mass, dry mass, and pH were used as the indicators for degradation. The 50-C-Mg/PLA composite (with coated wires) suppressed mass loss, controlled the pH, and promoted the deposition of Ca and P compounds. Further, the retention of tensile and flexural properties significantly improved for the immersion period as the interface was better protected by the coating. The results indicate that the 50-C-Mg/PLA composite has good potential as a biodegradable implant for load-bearing bone fractures.